Somatotype evolution in elite Spanish gymnasts - Busquets, A.; Irrutia, A.; Marina, M.; Galilea, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
To reach success in sport, many prerequisites depend on the physical condition, which include somatotype, body composition, and anthropometry (Claessens et al., 1999). In artistic gymnastics (AG) the upper body mesomorphy stands out. Nevertheless, the located body adaptations to training do not alter the general somatotype of the gymnast during adolescence more than expected by genetics (Malina, 1989). The present study describes, through a cross-sectional survey, the evolution of the somatotype and body composition with age of the Spanish elite gymnasts of both genders in comparison to normal Spanish values. Methods The results of other studies have been used to reflect the evolution of somatotype, free fat mass and fat mass rates: 1) Normal values of Spanish population; 2) Gymnastic values of other authors in males (MAG) and females (WAG) (Claessens et al., 1999; Calderone et al., 1986); 3) Growth values in a control population accepted by the international community (Malina & Bouchard, 1991; Malina, 1989); 4) Gymnastic data from the Olympic Training Center -CAR of San Cugat- since 1991 (n=150), and from a mixed cross-longitudinal Spanish gymnastics study (n=387; Marina & Rodríguez, 2001). Results The somatotype profile in gymnasts is ecto-endomorphic, but more mesomorphic in males (MAG) than in females (WAG). The lower endomorphy in gymnasts is the most differential parameter in comparison to Spanish control values, while the higher ectomorphy is the less distinctive. The mesomorphy presents a developmental profile different than in control population. The % of body fat in gymnasts is inferior to the Spanish population (MAG: 6.5%-12.3%; M. Reference: 13.0%-18.4%; WAG: 8.7%-13.5%; F. Reference: 15.1%-19.5%). It is confirmed that the accepted relative fat free mass (%FFM) increases in MAG from 10 (43.6%) to 22 years of age (51.3%), while in WAG the % FFM increase is observed until the age of 12. From 12 to 19 years old the % FFM is maintained, to decrease dramatically after 19. Discussion/Conclusion Limitations of a cross-sectional survey, a scarce number of studies about the evolution of somatotype and body composition in gymnasts (Calderone et al., 1986; Claessens et al., 1992), as well as methodological differences to measure both parameters, suggest caution to interpret the results. The evolution of the somatotype in WAG coincides with the ones described in the literature (Claessens et al., 1992). The absence of similar studies in MAG confines proper assessment and comparisons. The differences between gymnasts of both genders and control population from very young age suggest not only the effect of selection and genetics but also the effect of a very specific and intensive training. The lower body fat % in WAG in comparison to previous studies may be due to the combination of a strict diet and the training intensity and demand.